QUALITY OF TRAINING OF SHOTS FOR THE FOOD INDUSTRY AS THE FACTOR OF PROVIDING THE POPULATION WITH FOOD RESOURCES - Morozova E.A. (Техника и технология пищевых производств)
For full providing the population with food resources, among other things, requires proper training of relevant personnel. Their quality determines successful functioning of enterprises of the food industry and, above all, depends on the knowledge received by experts in educational organizations. For analysis the attitude of students of Kemerovo technological Institute of food industry (University) to the quality of professional training in the University, a questionnaire was conducted among students enrolled by the methods which include for the three elements: the level of students discipline, their skills, preparedness to work, and the final assessment of the quality of vocational training. The results showed that above the others was an indicator of the level of responsible attitude of students to learning, to discipline, but below - the level of their abilities, not only in the comparison of the three assessments with each other, but in comparison with the average data of nine educational institutions of higher education of the Kemerovo region. Identified problematic aspects, such as low achievement level of students, involvement in a future professional activity, insufficient attention to independent work and some others, allowed us to propose a number of considerations which should improve the quality of training of specialists in the food industry and, as a consequence, in the perspective to improve the provision of the population with food.